Decarbonising Construction Logistics: The Role of Supplier-led Distribution and Integrated Warehousing - Dhawan, K; Tookey, J; Fredriksson, A; Tetik, M (Emerald, 2026)
Purpose – This study aims to examine how supplier-led distribution and integrated warehousing enhance transport efficiency and reduce embodied carbon in construction logistics. Focusing on plasterboard delivery in Auckland’s linear urban context, it examines how early supplier engagement and forward-stocking can reconfigure logistics operations to address spatial and operational challenges, decarbonising the construction supply chain. Design/methodology/approach – This case-based analysis uses empirical data from supplier-managed plasterboard distribution in Auckland to assess how logistics reconfiguration – supplier-led deliveries and integrated warehousing – impacts transport efficiency and carbon embodiment. Carbon outcomes are quantified using Environmental Product Declarations and New Zealand freight emissions benchmarks, with application of spatial analysis and supply chain modelling to evaluate the impacts of forward-stocking and supplier engagement on fragmented construction logistics. Findings – The study finds that supplier-led distribution, integrated warehousing and forward-stocking significantly enhance transport efficiency by consolidating deliveries and reducing vehicle movements, resulting in measurable embodied carbon reductions. It underscores the importance of early supplier engagement and spatially responsive logistics planning in addressing urban sprawl, demonstrating that reconfigured supply chains offer both operational and environmental benefits towards construction sector decarbonisation. Originality/value – The paper analyses the interplay of distribution, transport and warehousing in linear sprawl, proposing an integrated transport-driven warehousing model. It demonstrates improved efficiency through supplier-centric distribution and challenges status-quo transport life cycle assessment, typically overlooked due to data availability constraints. Theoretically, it extends employment of operations research, limited to manufacturing and freight transport, in construction as a defragmentation enabler. It also argues for municipalities to require logistics plans, to bridge policy-practice gaps.
Keywords: 3509 Transportation, Logistics and Supply Chains; 33 Built Environment and Design; 35 Commerce, Management, Tourism and Services; 3304 Urban and Regional Planning; 12 Responsible Consumption and Production; 1202 Building; 1503 Business and Management; 1504 Commercial Services; 3302 Building; 3507 Strategy, management and organisational behaviour; 4005 Civil engineering; Construction decarbonisation; Construction transport; Embodied carbon; Integrated warehousing; Logistics sprawl; Urban distribution